Business Model Design for New Business Development at PTB Dialysis Clinic Chain - Fasha, Cokhy Indira; Larso, Dwi (The Indonesian Journal of Business Administration, 2012)
PTB is subsidiary of B Company, a German health care supplier. Division AV of PTBB focuses on dialysis products and services. As Division AV started direct business in 2009, PTB expects it can be growth driver in 2011-2015. The research aims to recognize and create external opportunity in dialysis service provider, to explore internal resources, and to develop new business model of PTB dialysis center. Corporate entrepreneurship framework is applied to provide solution. The research methodology is qualitative approach by semi-structured interview. The discussion points are put business model framework and synthesized into PTBB dialysis service provider business model.The result shows key issues as external opportunity and internal resources. Kidney failure patient in Indonesia has huge potential because limited specialists and dialysis center capacity, expensive cost of treatment, and limited access to reimbursement scheme. Dialysis service is dominated by hospital-based dialysis unit. However, hospital-based dialysis unit capacity cannot fulfill demand of patients. Stand-alone dialysis clinic development is opportunity. However, it has challenges in complicated permit, higher investment, and lack of support in reimbursement. PTB has several internal resources that can be utilized.The proposed business model solution is standardized and interconnected dialysis clinic chain,. The dialysis clinic chain focus on JAMKESMAS/DA patients and untreated patients. To run this model, important activity is building relationship with coordinator, while important resources are standardized operation procedures and centralized IT. Keywords: Corporate Entrepreneurship, Business Model, Dialysis Center, Healthcare ServiceÂ